Daisy and the Beastie - Simmons, Jane. (Boston : Little, Brown, 2000)
Daisy and her little brother Pip encounter many different animals as they look all over the farm for the Beastie from Grandpa's story.
Keywords: Ducks -- Fiction; Domestic animals -- Fiction; Brothers and sisters -- Fiction